Evaluation of Potassium, Calcium and Sodium in Sickle Cell Subjects - Arunsi, Ogbonnaya Mba; Nnatuanya, Isaac; Okwareke, Kalu Nwankwo (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
Electrolyte imbalances in SCD patients are frequently overlooked despite their significant role in disease progression and complications. This study aimed to evaluate serum electrolyte levels—potassium, calcium, and sodium—in sickle cell disease (SCD) patients and assess their clinical implications. This study was conducted at Madonna University Teaching Hospital in Nigeria, it employed a case-control design involving 132 participants, comprising 74 confirmed SCD patients (HbSS) and 58 age- and sex-matched healthy controls (HbAA). Blood samples were analyzed using an ion-selective electrode, revealing significant differences in electrolyte levels between groups. Specifically, SCD patients exhibit a markedly elevated serum calcium (4.98 ± 0.86 mmol/L) compared to controls (2.23 ± 0.23 mmol/L), with p < 0.001; higher sodium levels (152.29 ± 2.62 mmol/L) compared to controls (138.48 ± 3.68 mmol/L), with p < 0.001, and significantly lower potassium levels (3.28 ± 0.40 mmol/L) compared with controls (4.44 ± 0.66 mmol/L, with p < 0.001. These results shows that these alterations may result from chronic hemolysis, renal impairment, and metabolic stress associated with SCD, with elevated calcium possibly linked to bone resorption and hemolytic activity, while decreased potassium may occur as a result of cellular leakage and renal losses. Elevated sodium levels could reflect dehydration and impaired renal handling. These electrolyte disturbances are clinically relevant, as they predispose patients to arrhythmias, bone demineralization, and kidney dysfunction, thereby complicating disease management. The findings underscore the importance of routine electrolyte monitoring in SCD to detect early imbalances and implement targeted interventions. The study concludes that electrolyte disturbances are significant in SCD pathophysiology and recommends integrating regular electrolyte assessment into standard care, alongside nutritional counseling and patient education on hydration. Further research across diverse populations is warranted to validate these findings and elucidate underlying mechanisms, ultimately aiming to reduce morbidity and improve clinical outcomes in SCD patients.